Consumer Tax in Islam - Dwi Hanif Febriansyah (Al-Mahkamah: Islamic Law Journal, 2025)
A country is prohibited from collecting the wealth of its citizens without any underlying law. Tax is one of the main products of the state and is an important part of financial policy. Scholars argue based on ijtihad that tax (dharbah) is permissible and arises for reasons that are different obligations to the wealth of Muslims compared to zakat. The other side says that there is no tax (which is detrimental) that is permissible or impermissible according to Sharia. Many scholars argue that tax is prohibited and some argue that it is permissible, then we can see tax law, especially in Indonesia, with the maqashid of Sharia. If analyzed with the view of two levels of maqashid of Sharia according to As-Syatibi: Al-Daruriyah & Al-Hajjiyyah. So it can be concluded that consumer tax law is permissible for the sake of the benefit and must be obeyed by those who are obliged to pay consumer tax so that it does not become an unwanted dharuroh.